RANCANG BANGUN KOMPONEN TUMPUAN PENDORONG KAYU CHIP PADA CHAIN FEED TO CHIPPER - BONI HIDAYAT (Fakultas Teknik UMRI, 2020)
Chain Feed to Chipper is one of the equipment in the Wood Handling machine of the paper company PT. Indah Kiat Pulp & Paper Perawang, whose main function is to carry logs before chipping by the Chipper machine as raw material for making Pulp, but in the process it works Chain The feed has not been damaged at the deadline, namely the bearings of the Chain Feed made of solid iron are damaged, loose and enter the Chipper engine, thus damaging the parts in the Chipper engine, this of course requires a large cost in repairing the parts that are Therefore, research on the cause of damage or bearing limits of the Chain Feed was carried out and finally redesigned the Chain Feed, namely redesigning it by removing the bearings on the chain, by designing adding a triangular plate to replace the bearings as a means of carrying logs on the chain. Chain Feed. After re-designing the Chain Feed, the risk of damage to the bearings entering the Chipper engine is no longer there